The distributional impact of structural transformation in rural India: Model-based simulation and case-study evidence - Chris Elbers; Peter Lanjouw (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The North Indian village of Palanpur has been the subject of close study over a period of six decades from 1957/8 to 2015. Himanshu et al. (2018) have documented the evolution of the village economy over this period in an exhaustive study entitled How Lives Change: Palanpur, India and Development Economics, and point to two distinct, and staggered, drivers of growth and distribution of income. An early period of agricultural intensification associated with the green revolution saw an expansion of irrigation and the introduction of new agricultural technologies, leading to rising incomes accompanied by falling poverty and fairly stable, or even declining, income inequality. Subsequently, from about the mid-1970s onwards, a cumulative process of non-farm diversification took hold, and was accompanied by further growth and poverty decline, but also a significant rise in income inequality. This process of structural transformation is likely to be occurring more broadly in rural India. In this paper, we construct a simple model of a village economy that captures several of the salient elements of the Palanpur economy and society. We show that this basic model is readily able to reproduce the distributional outcomes observed in the village. We suggest that to the extent that there exist other villages in rural India with such features, similar distributional outcomes might be expected. We indicate, further, that while the non-farm diversification phase of the village growth story was accompanied by rising inequality, the counterfactual of no diversification might well have been associated with an even greater increase. We suggest that non-farm diversification has arguably helped to contain growth in inequality and has played a particularly pronounced role in reducing poverty.
Keywords: O18; O15; I32; C51; 330; income inequality; non-farm employment; poverty; rural diversification; simulation model; village study